Students’ Movement as “Detik” Cadre to Improve “PHBS” and Making School of Mosquito Larvae Free - Siti Mariam (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2019)
MI Nyatnyono 02 West Ungaran District of Semarang Regency is used as a model to create a school of mosquito larvae free. The method of these activities used participatory action research. The Detik program is the realization of Jumantik, foster and train students to monitor larvae around school and their own home by filling up the form. The activities involved 50 students of fourth and fifth graders. They were coached with dengue prevention learning materials. The activities were carried out for five days consisting of training and coaching, the competition to create bulletin boards and environmental movement by planting mosquito repellent plants such as lavender and geranium. The students fulfill the form once a week. The teacher as Jumantik in charge then submits the monthly summary report to the Puskesmas to complete the periodic inspection of larvae data within 3 months and then follow up. MI Nyatnyono 02 kecamatan Ungaran Barat, kabupaten Semarang digunakan sebagai model sekolah bebas jentik. Metode kegiatan ini adalah penelitian tindakan participatory. Program Detik (Detektif Jentik) adalah realisasi dari Jumantik (Juru Pemantau Jentik) yang membina dan melatih siswa untuk memonitor jentik dilingkungan sekolah dan rumah mereka dengan mengisi blangko. Kegiatan ini melibatkan 50 siswa kelas 4 dan 5. Mereka dibekali materi pembelajaran pencegahan demam berdarah dengue dan pemberantasan sarang nyamuk. Kegiatan ini berlangsung selama 5 hari yang terdiri dari pelatihan, pembekalan, lomba majalah dinding dan gerakan cinta lingkungan dengan menanam tanaman pengusir nyamuk seperti lavender dan geranium. Siswa mengisi blangko seminggu sekali dan menyerahkan kepada guru sebagai penanggung jawab jumantik disekolah. Selanjutnya diserahkan ke Puskesmas melengkapi data pemeriksaan jentik berkala setiap 3 bulan sekali dan kemudian ditindak lanjuti.